Golgi maturation‐dependent glycoenzyme recycling controls glycosphingolipid biosynthesis and cell growth via GOLPH3. (22nd March 2021) - Rizzo, Riccardo; Russo, Domenico; Kurokawa, Kazuo; Sahu, Pranoy; Lombardi, Bernadette; Supino, Domenico; Zhukovsky, Mikhail A; Vocat, Anthony; Pothukuchi, Prathyush; Kunnathully, Vidya; Capolupo, Laura; Boncompain, Gaelle; et al.
Abstract: Glycosphingolipids are important components of the plasma membrane where they modulate the activities of membrane proteins including signalling receptors. Glycosphingolipid synthesis relies on competing reactions catalysed by Golgi‐resident enzymes during the passage of substrates through the Golgi cisternae. The glycosphingolipid metabolic output is determined by the position and levels of the enzymes within the Golgi stack, but the mechanisms that coordinate the intra‐Golgi localisation of the enzymes are poorly understood. Here, we show that a group of sequentially‐acting enzymes operating at the branchpoint among glycosphingolipid synthetic pathways binds the Golgi‐localised oncoprotein GOLPH3. GOLPH3 sorts these enzymes into vesicles for intra‐Golgi retro‐transport, acting as a component of the cisternal maturation mechanism. Through these effects, GOLPH3 controls the sub‐Golgi localisation and the lysosomal degradation rate of specific enzymes. Increased GOLPH3 levels, as those observed in tumours, alter glycosphingolipid synthesis and plasma membrane composition thereby promoting mitogenic signalling and cell proliferation. These data have medical implications as they outline a novel oncogenic mechanism of action for GOLPH3 based on glycosphingolipid metabolism. SYNOPSIS: Glycosphingolipid (GSL) biosynthesis depends on the exact location and abundance of Golgi‐resident enzymes within the organelle stacks. Here, the Golgi membrane protein GOLPH3 is shown to control intra‐Golgi vesicular trafficking of GLS enzymes, promoting mitogenic signalling and proliferation in cancer cells. GOLPH3 dictates the sub‐Golgi localization of GSL biosynthetic enzymes by binding their cytosolic tails and incorporating them into COPI vesicles. GOLPH3 is a component of the cisternal maturation machinery. GOLPH3 promotes recycling of GSL enzymes counteracting their lysosomal degradation. GOLPH3 overexpression increases GSL enzyme levels enhancing GSL biosynthesis. Increased GSL biosynthesis promotes cancer cell proliferation. Abstract : The oncogene GOLPH3 regulates intra‐Golgi glycoenzyme retro‐transport, promoting mitogenic signalling and cancer cell proliferation.